Formulation and in vitro characterization of long-acting PLGA injectable microspheres encapsulating a peptide analog of LHRH. (10th February 2021) - Zhang, Chengqian; Wu, Lan; Tao, Anjin; Bera, Hriday; Tang, Xing; Cun, Dongmei; Yang, Mingshi
Abstract: The present study aimed to formulate triptorelin acetate (TA) into poly (D, L-lactic-co-glycolic) acid (PLGA) based injectable sustained-release microspheres (TA-PLGA-MS) by usingdouble emulsion solvent extraction/evaporation (DESE) technique and investigate the effects of various material attributes and process parameters on the quality attributes such as size, shape, surface morphology, encapsulation efficiency (EE) and in vitro release behavior of these microspheres. Variable compositions of the outer water phase, type of the organic solvents, volume ratios of inner water phase to oil phase, PLGA concentrations, and the powers for emulsification in the preparation of the microspheres showed an influence on their quality attributes. An optimal formulation (F-2) obtained from this univariate approach possess an excellent EE value of 63.5% ± 3.4% and an average volumetric particle size of 35.3 ± 1.8 μm. This formulation was further accomplished with different solidification rates assisted by variable incubation temperatures, which exhibited an impact on the shape/surface and inner morphology of the microspheres. The resultant microspheres also displayed different in vitro release patterns. The matrices processed with a high incubation temperature conferred the fastest and the most complete drug release profile over the period of 63 days. Thus, the solidification rate could be identified as one of the critical process parameters that affected the quality of the PLGA based injectable microspheres specifically designed for the prolonged delivery of TA.